2012
DOI: 10.1186/cc11408
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of a single recruitment maneuver after an apnea test for the diagnosis of brain death

Abstract: IntroductionMany potential lung transplants are lost because of hypoxemia during donor management. We hypothesized that the apnea test, necessary to confirm the diagnosis of brain death in potential lung donors, was involved in the decrease in the ratio of partial pressure of arterial O2 to fraction of inspired O2 (PaO2/FiO2) and that a single recruitment maneuver performed just after the apnea test can reverse this alteration.MethodsIn this case-control study, we examined the effectiveness of the recruitment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In our study blood gas analyses before and after apnea test suggests that apneic oxygenation method is reliable in the presence of appropriate pre-oxygenation. However Paries et al (14) showed that apnea test damages respiratory functions and suggested that lungsaving strategies, especially recruitment maneuvers should be routinely used after the test. An article about criteria for selection of receiver-donor for heart transplantation reported that 20-25% of organs, which are very hardly obtained indeed, were lost due to insufficient treatment of physiopathological responses occurred after brain death (15).…”
Section: Discussionmentioning
confidence: 99%
“…In our study blood gas analyses before and after apnea test suggests that apneic oxygenation method is reliable in the presence of appropriate pre-oxygenation. However Paries et al (14) showed that apnea test damages respiratory functions and suggested that lungsaving strategies, especially recruitment maneuvers should be routinely used after the test. An article about criteria for selection of receiver-donor for heart transplantation reported that 20-25% of organs, which are very hardly obtained indeed, were lost due to insufficient treatment of physiopathological responses occurred after brain death (15).…”
Section: Discussionmentioning
confidence: 99%
“…We wish to remind that the aim of our study [1] was not to compare the PaO 2 /FiO 2 ratio after apnea tests performed by disconnecting or not the patient from the ventilator. It was to show that hypoxemia after disconnection from the ventilator may be prevented by a single RM applied just after reconnection.…”
Section: Authors' Responsementioning
confidence: 99%
“…We read with interest the study by Marie Paries and collaborators [1]. Many potential lung transplants are lost because of hypoxemia after apnea test.…”
mentioning
confidence: 99%
“…For those patients who go on to become organ donors, atelectasis and higher pressures necessary to recruit the collapsed alveoli induced by apnea testing can cause significant injury and potentially decrease lung recovery rates. 7 The objective measure of lung quality used by most transplant surgeons is the P:F ratio, the ratio of the partial pressure of arterial oxygen (PaO 2 ) to fraction of inspired oxygen (FiO 2 ). The P:F ratio has been found to be significantly associated with organ recipient prognosis 8 and most transplant surgeons require a P:F ratio of >300 on a positive end expiratory pressure (PEEP) of 5 for eligibility.…”
Section: Introductionmentioning
confidence: 99%